TINJAUAN YURIDIS TERHADAP PENYERTAAN DALAM TINDAK PIDANA PASAL 279 AYAT (2) KUHP - Irena Aprilia Putri Basko; Dian Adriawan Dg. Tawang (Reformasi Hukum Trisakti, 2022)
Marriage is essentially one of the goals that every human being works toward in order to achieve many other goals, but in a marriage, a criminal conduct frequently occurs that is governed by the Criminal Code. One of them is paragraph (2) of Article 279, which governs crimes against marriage and origin. 260/Pid.B/2020/PN is the case number. Kdi contains a criminal act-marrying someone without their consent and keeping it a secret from other people. This is what inspired the development of this scientific paper using research techniques that include research objects in the form of criminal acts on the origin of marriage, followed by the type of normative law, with the nature of the research being descriptive analytical, with secondary data of the type, obtained by means of library research, and data analysis using qualitative data analysis methods. The conclusion that can be drawn from this research method is that the criminal act committed by the defendant was not properly terminated and the defendant's actions contained an element of inclusion with the theory that there were parties involved in the act.